Using Role Play Technique To Teach Speaking Skill Procedure Text In Tourism Department - Putu N R (IJET (Indonesian Journal of English Teaching), 2020)
In revolution idustri era 4.0 required the student in tourism department to enable speak english as internatinal language fluently. The students need to improve their communication skill. Role play technique is one teching technique that is applicable teaching technique in state polytechnic of Banyuwangi because it focused on practicing real life communication skill. The researcher tried to investigate the teaching speaking activity in the classroom. The study used descriptive qualitative research. The researcher analyzed and described the teaching speaking in procedure text by using role play technique for tourism department. The preparation of the lecturer was syllabus and learning contract which contained teaching materials, the method, and learning sources. The process of teaching was divided into three steps; they were pre-activity, main activity and post activity. He brought them in class. The lecturer used role play technique. The lecturer only facilitated the students to be motivated in learning speaking procedure text. He asked the students to do a simulation communication in a hotel. One of the students play role as reseptionist and the other as costumer. During teaching learning process, the lecturer got three main troubles in conducting teaching process. They were students’ low in vocabulary, pronunciation, and the students difficulty in expressing sentences and the lecturer had done the solution. speaking procedure text course which was taught by the lecturer proceded effectively and acceptable for the students. In revolution idustri era 4.0 required the student in tourism department to enable speak english as internatinal language fluently. The students need to improve their communication skill. Role play technique is one teching technique that is applicable teaching technique in state polytechnic of Banyuwangi because it focused on practicing real life communication skill. The researcher tried to investigate the teaching speaking activity in the classroom. The study used descriptive qualitative research. The researcher analyzed and described the teaching speaking in procedure text by using role play technique for tourism department. The preparation of the lecturer was syllabus and learning contract which contained teaching materials, the method, and learning sources. The process of teaching was divided into three steps; they were pre-activity, main activity and post activity. He brought them in class. The lecturer used role play technique. The lecturer only facilitated the students to be motivated in learning speaking procedure text. He asked the students to do a simulation communication in a hotel. One of the students play role as reseptionist and the other as costumer. During teaching learning process, the lecturer got three main troubles in conducting teaching process. They were students’ low in vocabulary, pronunciation, and the students difficulty in expressing sentences and the lecturer had done the solution. speaking procedure text course which was taught by the lecturer proceded effectively and acceptable for the students. In revolution idustri era 4.0 required the student in tourism department to enable speak english as internatinal language fluently. The students need to improve their communication skill. Role play technique is one teching technique that is applicable teaching technique in state polytechnic of Banyuwangi because it focused on practicing real life communication skill. The researcher tried to investigate the teaching speaking activity in the classroom. The study used descriptive qualitative research. The researcher analyzed and described the teaching speaking in procedure text by using role play technique for tourism department. The preparation of the lecturer was syllabus and learning contract which contained teaching materials, the method, and learning sources. The process of teaching was divided into three steps; they were pre-activity, main activity and post activity. He brought them in class. The lecturer used role play technique. The lecturer only facilitated the students to be motivated in learning speaking procedure text. He asked the students to do a simulation communication in a hotel. One of the students play role as reseptionist and the other as costumer. During teaching learning process, the lecturer got three main troubles in conducting teaching process. They were students’ low in vocabulary, pronunciation, and the students difficulty in expressing sentences and the lecturer had done the solution. speaking procedure text course which was taught by the lecturer proceded effectively and acceptable for the students.